FRI0353 Infliximab vs cyclophosphamide in pediatric takayasu's arteritis. (23rd January 2014) - Stern, S.; Clemente, G.; Reiff, A.; Ramos, M.; Marzan, K.; Terreri, M.T.
Abstract : Background: Pediatric Takayasu's Arteritis (pTA) is a rare granulomatous vasculitis that affects the aorta and its branches. Though cyclophosphamide (CYC) is often used as first line therapy there are few studies proving its efficacy (2). Recently, several case series have reported beneficial results with Infliximab (INF) treating adult and pediatric patients with TA (1). Objectives: To describe the treatment response to CYC and INF in an American and Brazilian cohort of pTA patients. Methods: Retrospective analysis of 23 pediatric Takayasu's Arteritis patients seen at Children's Hospital Los Angeles (CHLA) and Universidade Federal de São Paulo – Brazil (Unifesp) from 1990 to 2011. All patients fulfilled the 1990 American College of Rheumatology criteria for TA. Disease activity was assessed by angiographic imaging, markers of inflammation, and clinical findings. Outcome was assessed using a scoring system (-1 = worse, 0 = unchanged, 1 = improved) that was applied to imaging and clinical findings. Results: 23 pts (14F:9M), mean age at disease onset 9.0±3.8 yrs were included: 3 patients presented with type IIa, 2 with type IIb, 3 with type III, 2 with type IV, and 13 with type V (1994 International TA Conference criteria). There was a significantly longer time between disease onset and diagnosis in the Unifesp cohort (2.7±2.1 yrs) compared to the CHLA cohort (1.0±4.6 yrs) (p-value 0.027). CYC was used as initial treatment in 17/23 and INF in 2/23 patients. Average time from disease onset to initiation of CYC was 2.6±2.4 yrs and INF 4.1±2.4 yrs. 9/17 patients initially treated with CYC were changed to INF due to disease progression (7) or partial response (2). 7/9 of these patients subsequently clinically improved on INF. The 2 patients initially treated with INF were changed to CYC due to lack of appropriate response. 1 patient worsened on CYC and the other was lost to follow-up. Of the remaining 4 patients who did not receive CYC or INF 1 patient improved on methotrexate, 1 patient was treated with corticosteroids, methotrexate, and cyclosporine, and 2 patients died. The 2 fatalities were Unifesp patients who died prior to treatment with any immunosuppressant medications except corticosteroids. No differences were detected between the inflammatory markers or angiographic progression in the 2 treatment groups at 6, 12, 24, and 48 months. One serious adverse event occurred during CYC (sepsis) but none during treatment with INF. Conclusions: Pediatric Takayasu's Arteritis is difficult to treat and can lead to significant morbidity or mortality. CYC is often used in the treatment of pTA but has many potential side effects. INF was non-inferior to CYC in our study although patient numbers were too low to detect meaningful statistical differences. Use of INF may be an alternative therapeutic option in pediatric patients with TA. References: Hoffman GS, et al. Anti-tumor necrosis factor therapy in patients with difficult to treat Takayasu's arteritis. Arthritis Rheum 2004; 50:2296-304. Ozen S, et al. Takayasu arteritis in children: Preliminary experience with cyclophosphamide induction and corticosteroids followed by methotrexate. J Pediatr 2007; 150:72-6. Disclosure of Interest: S. Stern: None Declared, G. Clemente Consultant for: Novartis, A. Reiff Consultant for: Immunex, Wyeth, Amgen, Merck, Abbott, Pfizer, Novartis, & Genentech, M. Ramos: None Declared, K. Marzan: None Declared, M. T. Terreri Consultant for: Novartis, Pfizer, Johnson & Johnsons, & Abbott